A Method of Measurement Parameters Programmatically Configuring for Traction Inverter Based on LabVIEW - 陈明奎; 谭利红 (机车电传动)
A method of measurement parameters programmatically configuring based on LabVIEW was introduced. The technique of modifying measurement parameter in human machine interface was discussed in detail, in which many advanced programming techniques, for example, applying VI reference, property node calling, controls references indexing, genetic reference converting to specific reference, were applied. The module of measurement parameters programmatically configuring in measurement system extended the software’s suitable scope and it is beneficial to software’s modularization and reuse.